Narrating Karma and Rebirth : Buddhist and Jain Multi-Life Stories / [electronic resource] - Appleton, Naomi (Cambridge : Cambridge University Press, 2014)
Buddhism and Jainism share the concepts of karma, rebirth, and the desirability of escaping from rebirth. The literature of both traditions contains many stories about past, and sometimes future, lives which reveal much about these foundational doctrines. Naomi Appleton carefully explores how multi-life stories served to construct, communicate, and challenge ideas about karma and rebirth within early South Asia, examining portrayals of the different realms of rebirth, the potential paths and goals of human beings, and the biographies of ideal religious figures. Appleton also deftly surveys the ability of karma to bind individuals together over multiple lives, and the nature of the supernormal memory that makes multi-life stories available in the first place. This original study not only sheds light on the individual preoccupations of Buddhist and Jain tradition, but contributes to a more complete history of religious thought in South Asia, and brings to the foreground long-neglected narrative sources.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Karma; Reincarnation